Cerebral Venous Sinus Thrombosis: An Uncommon Presentation of Headache Mimicking Subarachnoid Hemorrhage (Journal of Medicine, 2009)
Cerebral venous sinus thrombosis is a rare disorder accounting for less than 1% of all strokes. It is more common in children and young adults. Here we report a rare and interesting case of cerebral venous l sinus thrombosis mimicking subarachnoid hemorrhage. A 40 years old women, presented with sudden onset of headache, vomiting and unconsciousness associated with convulsions. She had a history of taking oral contraceptives for the last 12 years. Clinical examinations showed ill-looking women with Glasgow Coma Scale of 12 along with neck rigidity and bilateral papilloedema. Although initially we suspected her as a case of subarachnoid hemorrhage, subsequent investigations with MRI and MRV showed to be a case of superior sagittal and transverse sinus thrombosis. Treatment with anticoagulation recovered her from headache and papilloedema. Serum levels of thrombophilic factors were within the normal physiological limits. Thus we concluded that although cerebral venous thrombosis is 100 times less than the cerebral arterial disease, a women presented with sudden onset of headache and vomiting with long term use of oral contraceptives, cerebral thrombosis should be considered as a differential.  Key words: Cerebral venous sinus thrombosis , Sagittal sinus thrombosis, Subarachnoid hemorrhage , Magnetic resonance venography. doi: 10.3329/jom.v10i2.2826   J MEDICINE 2009; 10 : 115-118